TRANSPLANTASI HUKUM DI NEGARA-NEGARA ASIA: SUATU PERBANDINGAN - Syahriza Alkohir Anggoro (Universitas Muhammadiyah Malang, 2021)
This research discusses legal transplants in Asian countries. Legal transplantation (legal transplantation) is a theory that began to be widely used by some comparative and socio-legal law scholars in the mid-1970s. Using a normative juridical research method, this study chooses a historical, comparative, case and conceptual approach in examining legal transplantation in Asian countries. The results of this study indicate that there are two types of legal transplants carried out by common law and civil law countries in Asia, namely historical legal transplants and practical legal transplants.